Pemanfaatan barang bekas dalam bercocok tanam secara hidroponik bagi masyarakat pesisir - St. Fatmah Hiola; Nur Anny Suryaningsih Taufieq; Putri Humaira Salsabila (Universitas Negeri Makassar, 2020)
One of the potentials that according to most people is worthless is rubbish. Garbage is a consequence of human activity. Plastic waste is one of the types of waste whose existence dominates the human environment. One technique for reusing inorganic waste can be done by making used goods as agricultural containers, besides being cheap, easy to obtain, durable, and also able to reduce the level of pollution to the environment. This dedication activity is carried out using training methods. The number of participants as many as 25 people who are communities around the coastal region, namely in the Village Turikamaseng, Maros Regency, South Sulawesi Province. The results of the activities showed that the interests and skills of the community after attending the training activities increased. The material given in the opinion of the community is quite interesting and can be applied directly in their daily lives. The conclusion that is able to provide an understanding of the importance of protecting the environment around us. In addition, the methods used in this activity have been able to improve the knowledge and skills of partner communities in terms of knowledge about hydroponic farming.